A Novel of Energy Consumption Profile of a Shopping Center - Ruliyanta, Ruliyanta; Setyadi, Wismanto; Kusumoputro, R. A. Suwodjo (Universitas Ahmad Dahlan, 2023)
Energy conservation in Indonesia is the primary choice made by the government of the Republic of Indonesia. It is undeniable that the highest consumption of a building is air conditioning energy, especially in a tropical environment like Indonesia. Air conditioning consumes between 40% and 80% of power in a high-rise building. The problem is how to find out the electricity usage profile and energy consumption index in a building that has been in operation for more than 20 years. This research aims to find the energy profile and calculate the energy consumption of a shopping center building. The method used is an Energy Audit according to SNI 6196. The energy consumption profile is an anomaly where the energy consumption for the air conditioning system is only 48%, while the average value in shopping centers in Indonesia is 62.9%. Meanwhile, the GFA energy consumption index is 23.11 kWh/m2/month or 277.3 kWh/m2/year. According to SNI 03-0196, the result is classified as an energy-intensive building. This value is close to the SNI 03-0196 standard for very energy-intensive building levels, which has values between 23.75 and 37.5 kWh/m2/month. Energy-saving opportunities are calculated by calculating the difference in the ECI value with the target ECI value. To increase the efficiency of energy consumption, this can be done by replacing the chiller unit which still uses a step type compressor. Apart from that, improving air conditioning insulation is very significant to overcome energy consumption problems. Adding green plants around buildings can also increase electrical efficiency.